Evaluation of the effectiveness of Continuous Infusion Pump (CIP) in pain control in the recovery period after thoracic surgery (Research, Society and Development, 2022)
Objective: to verify the effectiveness of epidural block in a continuous infusion pump (BIC), without pain control in the postoperative period of thoracic surgery. Methodology: cross-sectional study, using a database carried out at the Center for Oncological Research (CEPON), in patients undergoing thoracic surgery from 2018 to 2020, in patients undergoing a thoracotomy. For data analysis, the IBM Statististicsl Package for the Social Sciences (IBM SPSS®) 18.0 program was used, in the descriptive analysis of the dependent variable Visual Analog Scale of Pain and Length of Stay in the ICU, using the Mann-Whitney U Test . Quantitative data generated by measures of central tendency (average) and their variability/dispersion and qualitative measures in the form of simple and relative frequencies. Study approved by the research ethics committee. Results: in this series, they were due to 35 patients who underwent thoracic surgery, the most prevalent male (57.1%), mean age 56.63 and mean ICU length of 2.78. The most frequent surgery for lobectomy (51.7%). The Mann-Whitney U Test leaves group 1 reporting less pain than group 2 at POi (p = 0.035). an average length of stay in the ICU was observed for patients in group 1 (3.67 ± 1.63). Conclusion: the study, the use of epidural block in BIC with superior efficacy in controlling postoperative pain in the sample undergoing thoracic surgery at CEPON, also observed a longer length of stay in the ICU of patients who used this anesthetic modality.